La obra de Clarice Lispector como medio de subjetivizacion en clases de Lengua Portuguesa - Leandro Aparecido Fonseca; Juracy Machado Pacífico; Elaine Rodrigues Nichio; Ana Maria de Lima Souza (Universidade Federal de Rondônia, 2019)
The article highlights the subjectivation present in Clarice Lispector texts as an instrument that enables the reader / reader-student / student to enter into the text deepest layers and thereby achieve the humanizing character derived from literary art. From the studies of the works "Passion according to G.H." and "Living Water" were produced reviews that aimed, through the construction of the characters, to present reflections that make possible the work in the classroom considering the student / student-subject in their own existential, spiritual and intimate dimensions. The text shows that Lispector 's literature is for the male or female Portuguese teacher a transformation tool for the he or she student, since it enables human edification through an approach that joins knowledge of art, philosophy, sociology and psychology.